Invasin of Yersinia pseudotuberculosis is not a polyclonal activator of mouse B lymphocytes - De Medeiros, Beatriz Maria Machado [UNESP]; Cangiani, E. E. [UNESP]; Higuti, L. [UNESP]; Satomi, L. C. [UNESP]; Souza, C. D. [UNESP]; Silva, A. R C [UNESP]; Maia, J. M L [UNESP]; Falcão, D. P. [UNESP] (My University, 2006)
It is known that the invasin molecule of Yersinia pseudotuberculosis stimulates human peripheral B cells in vitro. In this work we evaluated the in vivo role of invasin as polyclonal activator of B lymphocytes in the mouse experimental model, by comparing strains of Y. pseudotuberculosis expressing invasin and isogenic inv mutants. Swiss mice were infected intravenously with two strains expressing invasin (YpIII pIB1 and an isogenic virulence plasmid-cured strain, YpIII) and with two invasin mutant strains (Yp100 pIB1 and Yp100, plasmid-cured). Spleen cells were sampled on days 7, 14, 21 and 28 after infection. Immunoglobulin (Ig)-secreting spleen cells were detected by protein A plaque assay and specific antibodies were detected in sera by ELISA. The virulent strain YPIII pIB1 (wild type) did not provoke polyclonal activation of B lymphocytes in vivo. In general, fewer Ig-secreting spleen cells of all isotypes were found in the infected animals than in the control animals. Specific IgG antibodies were detected in the sera of animals infected with all strains. The peak response occurred on the 21 st day post-infection, and the Yp100 strain provoked the highest level of these antibodies. We concluded that invasin is not a polyclonal activator of murine B cells.
Keywords: B lymphocytes; Invasin; Polyclonal activation; Specific antibodies; Yersinia pseudotuberculosis; immunoglobulin; invasin; protein A; analytic method; animal experiment; B lymphocyte activation; bacterial strain; comparative study; controlled study; enzyme linked immunosorbent assay; female; mouse; nonhuman; spleen cell